Understanding socio-sexual networks: critical consideration for HIVST intervention planning among men who have sex with men in Kenya - Lisa Lazarus; Ravi Prakash; Bernadette K. Kombo; Matthew Thomann; Kennedy Olango; Martin K. Ongaro; Samuel Kuria; Memory Melon; Helgar Musyoki; Souradet Shaw; Parinita Bhattacharjee; Robert Lorway (BMC, 2022)
Abstract Background HIV self-testing (HIVST) has emerged as a way of reaching individuals who may be less likely to access testing, including men who have sex with men (MSM). Understanding the social networks of MSM is key to tailoring interventions, such as HIVST, for particular locations. Methods We undertook a socio-sexual network study to characterize and identify patterns of connection among MSM and inform an HIVST intervention in three sites in Kenya. Community researchers in each site selected eight seeds to complete a demographic form and network surveys for 15 each of their sexual and social network members. Seeds recruited three respondents, including two regular service users and one MSM who was "unreached" by the program, who then each identified three respondents, resulting with data on 290 individuals. Results Findings illustrate the interconnectedness of community-based organization (CBO) members and non-members. In networks where a majority of members had a CBO membership, members had better contacts with programs and were more likely to have accessed health services. Larger networks had more HIV testing and seeds with frequent testing had a positive influence on their network members also being tested frequently. HIVST was tried in very few networks. Almost all network members were willing to use HIVST. Conclusion Willingness to use HIVST was nearly universal and points to the importance of networks for reaching individuals not enrolled in programs. Network analysis can help in understanding which type of networks had higher testing and how network-based approaches can be useful to promote HIVST in certain contexts.